room # - Synnos, Nicos (My University, 2020)
ROOM# (2020) Video installation. Experimental, stop motion animation-video Forest Park, silent witness of the physical presence of Daphne du Maurier and a hyperspace of multiple realities, constitutes the ideal context for the quest of a relation between the past and the present that aspires to associate the author and her work with the wider space, the island. Nicos Synnos' artwork is shown through video surveillance of du Morier's room, both as a confession of our voyeuristic disposition vis-à-vis the lives of others, but also as a reminder of the fact that the present, the dominant flowing time, is constantly and interactively projected onto a quest and domestication of the past. Synnos uses fragments of photographs and animation experiments to construct fictional images in a video. By placing the action on the ongoing cinematic present, the intertwines the fictional with the historical to construct a multi-temporal visual "reality".